Dry Powder Comprised of Isoniazid-Loaded Nanoparticles of Hyaluronic Acid in Conjugation with Mannose-Anchored Chitosan for Macrophage-Targeted Pulmonary Administration in Tuberculosis - Mahwash Mukhtar; Noemi Csaba; Sandra Robla; Rubén Varela-Calviño; Attila Nagy; Katalin Burian; Dávid Kókai; Rita Ambrus (MDPI AG, 2022)
Marketed dosage forms fail to deliver anti-tubercular drugs directly to the lungs in pulmonary Tuberculosis (TB). Therefore, nanomediated isoniazid (INH)-loaded dry powder for inhalation (Nano-DPI) was developed for macrophage-targeted delivery in TB. Mannosylated chitosan (MC) and hyaluronic acid (HA) with an affinity for the surface mannose and CD44 receptors of macrophages were used in conjugation to prepare hybrid nanosuspension by ionic gelation method using cross-linker, sodium tri-polyphosphate (TPP) followed by freeze-drying to obtain a dry powder composed of nanoparticles (INH-MC/HA NPs). Nanoformulations were evaluated for aerodynamic characteristics, cytotoxicity, hemocompatibility, macrophage phenotype analysis, and immune regulation. Cellular uptake imaging was also conducted to evaluate the uptake of NPs. The nanopowders did not pose any significant toxicity to the cells, along with good compatibility with red blood cells (RBCs). The pro-inflammatory costimulatory markers were upregulated, demonstrating the activation of T-cell response. Moreover, the NPs did not show any tolerogenic effect on the macrophages. Furthermore, confocal imaging exhibited the translocation of NPs in the cells. Altogether, the findings present that nano-DPI was found to be a promising vehicle for targeting macrophages.